Nursing care for pregnant women deprived of liberty (Research, Society and Development, 2024)
It is a textual production based on the health care of women with deprivation of liberty who are going through a gestational state with the objective of showing in scientific productions about prenatal care for pregnant women in prison in Brazil, in what guides the performance of nursing in this line of health care. Methodology: This is a Narrative Review of descriptive analysis with a qualitative approach with data collection through the databases of the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), Nursing Database (BDENF) and Public Platforms. The results were composed of 20 publications followed by the authors' discussions. Final Considerations: consider that the structure of the prison system, regarding women's health care, should follow the guidelines of the Primary Care Protocols for prenatal care.  They also emphasize that pregnant women deprived of liberty must be assisted by a health professional composed of the multidisciplinary team, which includes welcoming actions from the initial phase of pregnancy to the moment of delivery and postpartum, as it is guaranteed by law.